Food Adulteration: Awareness and Consumer Perception among urban households of Kanpur, Uttar Pradesh - Rashmi Singh; Aelena Takhellambam; Avantika Awashthi (Public Health, 2026)
Food adulteration poses a significant public health risk in India, compromising the safety and nutritional quality of commonly consumed food items. This study aimed to assess the knowledge, awareness, and practices related to food adulteration among residents of Kanpur, Uttar Pradesh. A total of 120 respondents, who regularly purchased food for household consumption, were selected using probability sampling and a simple random cluster method. The sample size was calculated using the RAOSOFT sample size calculator, assuming a 95% confidence level, 5% margin of error, and 10% response distribution. Data were collected through a pretested questionnaire covering respondents’ understanding of food adulteration, commonly adulterated items, adulterants used, and traditional household detection methods. The results indicated that most respondents (76.7%) correctly understood the concept of food adulteration, with milk, cereals, pulses, edible oils, red pepper, and jaggery frequently reported as adulterated. Traditional detection methods, such as handpicking, water tests, visual inspection, and boiling tests, were widely practised, though awareness of chemical-based detection was limited. Only 60% of respondents were aware of regulatory authorities like FSSAI. Overall, the findings suggest satisfactory general awareness about adulteration and its health risks, but highlight the need for targeted consumer education and public awareness programs to improve detection practices, regulatory knowledge, and ensure safer food consumption in Kanpur.